TECHNICAL TRAINING OF THE FUTURE TEACHER - Jahona Karimova (American Journals, 2023)
In this article, it is mentioned about the organization and management of the processes of formation of technological skills among elementary school teachers, analysis and improvement based on prioritization of subject relations in pedagogical activities.